THE ROLE OF SIDIS V. F-R PUBLISHING CO. CASE IN THE FORMATION OF RIGHT TO BE FORGOTTEN - Lytvynenko, Anatoliy (Teisė, 2017)
The given article displays the case of Sidis v. F-R Publishing Co., which features a suit of a former adolescent prodigy, William Sidis against the New Yorker newspaper for publishing an article “Where Are They Now? April Fool” where his biography as well as a then-present style of life were portrayed. This case possesses a particular concordance for the theory of “right to be forgotten” as a derivative of right to privacy in common law as well as having triggered the issues of celebrity-related public interest and article newsworthiness tests applied by US courts in later cases.